Answers

The Brainliest Answer!
2014-05-10T13:34:54+05:30
Since α and β are zeros of the polynomial the polynomial is (x-α)(x-β).
  therefore p(x) = (x-α)(x-β)
               x^2-5x+k = (x-α)(x-β)
               x^2-5x+k = x^2-(α+β)x+αβ
      equating the coefficients of x on both sides we get,
                 α+β = 5....(1)
     equating the constants on both sides we get αβ = k ...(2)
        We have α-β = 1 .....(3)
      Solving (1) and (3) we get α=3 and β = 2
          therefore k = αβ
                           =3*2
                           = 6
     
2 5 2
2014-05-10T14:18:08+05:30
Alpha+beta=-5/-1=5        
alpha*beta=k              (Sum of roots=-b/a,prod. of roots=c/a for ax^2+bx+c=0)
from the given hint,
(5^2)=(1^2)+4k
25=1+4k
24=4k
=>k=6
1 5 1